2007
DOI: 10.1194/jlr.m700301-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the regulatory oxysterol, 5-cholesten-3β,25-diol 3-sulfate, in hepatocytes

Abstract: Cellular cholesterol homeostasis is maintained through coordinated regulation of cholesterol synthesis, degradation, and secretion. Nuclear receptors for oxygenated cholesterol derivatives (oxysterols) are known to play key roles in the regulation of cholesterol homeostasis. We recently identified a sulfated oxysterol, 5-cholesten-3b,25-diol 3-sulfate (25HC3S), that is localized to liver nuclei. The present study reports a biosynthetic pathway for 25HC3S in hepatocytes. Assays using mitochondria isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 35 publications
(54 reference statements)
1
83
0
1
Order By: Relevance
“…25-Hydroxy-cholesterol and other oxysterols suppress cholesterol biosynthesis by suppressing proteolytic activation of SREBP-2 ( 23 ). Although 25-hydroxy-cholesterol is also produced by microsomal cholesterol 25-hydroxylase ( 42 ), mitochondrial CYP27A1 ( 43,44 ), and nonenzymatic autoxidation of cholesterol ( 45 ), results of the present study showed that levels of 25-hydroxy-cholesterol in the livers of Cyp3a Ϫ / Ϫ mice were signifi cantly lower than those in WT mice ( Table 1 ). Therefore, it is suggested that defi ciency of CYP3A leads to reduction of 25-hydroxy-cholesterol synthesis, resulting in activation of SREBP-2.…”
Section: Effects Of Cyp3a Defi Ciency On Expression Levels Of Cholestmentioning
confidence: 57%
“…25-Hydroxy-cholesterol and other oxysterols suppress cholesterol biosynthesis by suppressing proteolytic activation of SREBP-2 ( 23 ). Although 25-hydroxy-cholesterol is also produced by microsomal cholesterol 25-hydroxylase ( 42 ), mitochondrial CYP27A1 ( 43,44 ), and nonenzymatic autoxidation of cholesterol ( 45 ), results of the present study showed that levels of 25-hydroxy-cholesterol in the livers of Cyp3a Ϫ / Ϫ mice were signifi cantly lower than those in WT mice ( Table 1 ). Therefore, it is suggested that defi ciency of CYP3A leads to reduction of 25-hydroxy-cholesterol synthesis, resulting in activation of SREBP-2.…”
Section: Effects Of Cyp3a Defi Ciency On Expression Levels Of Cholestmentioning
confidence: 57%
“…THP-1 macrophages express SULT2B1b and are able to synthesize 25HC3S (38). It has been reported by our laboratory that the expression is dramatically upregulated by insulin and downregulated by 25HC3S in both hepatocytes (36) and macrophages (38). In vitro, only 5% of our added 25HC3S entered the cells.…”
Section: Discussionmentioning
confidence: 96%
“…Macrophages are able to synthesize this oxysterol (38). This oxysterol appears to be synthesized from 25-hydroxycholesterol (25HC) by sterol sulfotransferase-2B1b (SULT2B1b) (36). Overexpression of SULT2B1 impairs the response of oxysterol receptor liver X receptor (LXR) to multiple oxysterol ligands.…”
mentioning
confidence: 99%
“…It also is capable of carrying out further oxidation of the 27-hydroxy group to yield a C-27 carboxyl group. Finally, this enzyme also has the ability to 25-hydroxylate cholesterol, yielding a potentially important regulatory oxysterol, 25-hydroxycholesterol ( 37 ). 25-Hydroxycholestrol can be further metabolized in hepatocytes to 25-hydroxycholesterol-3-sulfate.…”
mentioning
confidence: 99%